Modeling and simulation for the distribution of slurry particles in chemical mechanical polishing - Nguyen, N. Y. (2016)
Slurry plays an important role in the material removal of chemical mechanical polishing (CMP). However, the behavior of abrasive particles of the slurry in the interface between the wafer and the pad during CMP is not fully understood. In this paper, a new computational fluid dynamic (CFD) model was developed. It was a combination of multiphase and discrete phase modeling. The abrasive particles behavior and the slurry distribution in the interface were simulated using this model. The total numbers of particles in the gap were quantified to characterize their mechanical effects under different operating parameters. The simulation results showed that when the gap thickness increased and speeds of the wafer and the pad decreased, the total number of particles in the gap increased. It also found that the particles were non-uniformly distributed below the wafer. The results have the capacity of providing a deeper insight understanding of the material removal of the CMP mechanism.